(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Higher levels of competition rank have significant influence on the structure and shooting performance in youth basketball. The aim of the study was to investigate the interaction of shooting and match results of Lithuanian female youth national team players dependent on the competition level. Research methods. The basketball players (n = 7) of the Lithuanian Basketball Centre were investigated. The performance indicators of those players were analyzed on the basis of the data collected during the Lithuanian Women “A” league and European Basketball Championship of 2011. We analyzed the statistics of six selected key indicators: 2- and 3- point field goal attempts, free-throws. The data were processed by SPSS 17.0 for Windows. Person’s correlation coefficients were calculated to determine the relationships between the match results within all shooting types and different players. Research results. The top efficacy of shooting was found in Lithuanian Championship (LC), the lowest – in European Championship (EC). The highest efficiency of free throws was found in the II nd period (62.53%), two- points (44.74%) and three-points (19.45%) shooting efficacy in the I st period in LC. Seven players of LBC in Lithuanian Championship earned the majority part of all points i. e. 74% in the I st period and 75% in the II nd period. However, the contribution of 7 players of LBC in the international competition level of EC was less, 59% of total team points. Discussion and conclusions. Though the players performed successfully and efficiently in both stages of LC and won all matches with a great difference in points, remarkable decrease in shooting efficacy and winning one match only (out of 9) in EC might be considered as not adequate level of mastership in the opponents’ teams in LC or not adequate individual level of sport performance. Lithuanian basketball federation should rethink the system of targeted training of the Lithuanian youth team during the preparatory period in order to manage suitable local competition level for better advance in the performance at the international level. Keywords: sport performance, sport games, sport contest model, shooting efficacy in basketball.